Safety tests and clinical research on buccal and nasal microneedle swabs for genomic analysis - Kim, JeongHyeon; Moon, Jae-Woo; Kim, Gyeong Ryeong; Kim, Wonsub; Hu, Hae-Jin; Jo, Won-Jun; Baek, Seung-Ki; Sung, Gil-Hwan; Park, Jung Ho; Park, Jung-Hwan (Frontiers in Bioengineering and Biotechnology, 2023)
Conventional swabs have been used as a non-invasive method to obtain samples for DNA analysis from the buccal and the nasal mucosa. However, swabs may not always collect pure enough genetic material. In this study, buccal and nasal microneedle swab is developed to improve the accuracy and reliability of genomic analysis.A cytotoxicity test, a skin sensitivity test, and a skin irritation test are conducted with microneedle swabs.Polymer microneedle swabs meet the safety requirements for clinical research and commercial use.When buccal and nasal microneedle swabs are used, the amount of genetic material obtained is greater than that from commercially available swabs, and DNA purity is also high. The comparatively short microneedle swab (250 μm long) cause almost no pain to all 25 participants. All participants also report that the microneedle swabs are very easy to use.When genotypes are compared at five SNP loci from blood of a participant and from that person's buccal or nasal microneedle swab, the buccal and nasal microneedle swabs show 100% concordance for all five SNP genotypes.Microneedle swabs can be effectively used for genomic analysis and prevention through genomic analysis, so the utilization of microneedle swabs is expected to be high.